2021
DOI: 10.3389/fmolb.2021.670160
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Alters the m6A Epitranscriptomic Tagging of RNAs in Cardiac Tissue

Abstract: N6-methyladenosine (m6A) modification plays important roles in the pathology of a variety of diseases. However, the roles of m6A modification in sepsis-induced myocardial dysfunction are not well defined. Rats were divided into control and lipopolysaccharide (LPS)-induced sepsis group. Global m6A levels of left ventricle tissue were measured by LC-MS/MS, and transcriptome-wide m6A modifications were profiled using epitranscriptomic microarrays (mRNAs and lncRNAs). Bioinformatics analysis was conducted to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The emerging roles of m 6 A modification on sepsis-induced organ dysfunction have been gradually verified [ 26 28 ]. For example, in lipopolysaccharide (LPS)-induced endotoxemia on myocardial inflammation, the m 6 A-RNA methylation level and inflammatory cytokine genes increased, while FTO knockdown mimicked the effects [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emerging roles of m 6 A modification on sepsis-induced organ dysfunction have been gradually verified [ 26 28 ]. For example, in lipopolysaccharide (LPS)-induced endotoxemia on myocardial inflammation, the m 6 A-RNA methylation level and inflammatory cytokine genes increased, while FTO knockdown mimicked the effects [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… Shen et al (2021) found that decreased m 6 A levels of lncRNA-XR_343955 in rat aortic tissue affect the inflammatory response through the cell adhesion molecule pathway during lipopolysaccharide-induced sepsis. The decrease in m 6 A modification of lncRNA XR_346,771 may be related to cation import in rat cardiac tissue during sepsis ( Han et al, 2021 ). Moreover, the function of lncRNA is closely related to their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…m6A methylation pattern in cardiac tissue of septic shock rat model was found to be significantly different from control rat. Additionally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that differentially m6A-methylated mRNAs are mainly involved in interleukin-17 (IL17) signaling pathways, TNF signaling pathway, and cytokine receptor interaction pathway, suggesting that m6A methylation possibly participate in the progression of septic cardiomyopathy through immune and inflammatory response ( Han Y.-C. et al, 2021 ; Shen Z.-J. et al, 2021 ).…”
Section: M6a Methylation and Cvdsmentioning
confidence: 99%